The Influence of Business Risk and Corporate Governance on Share Prices with Moderating Variables Dividend Policy in Banking Companies Listed on the Indonesian Stock Exchange in 2021-2023 - Rachel Nayna Sofyamitha; Dwi Ermayanti Susilo (Yayasan Adra Karima Hubbi, 2024)
Background. Share prices reflect the performance and investors' perceptions of company prospects, including those in the banking sector. Business risk and corporate governance influence share prices, while dividend policy can strengthen or weaken this relationship. This research is important to understand these dynamics in banking companies listed on the IDX during the 2021-2023 period, considering the post-pandemic economic challenges. Purpose. This research aims to examine the influence of business risk and corporate governance on share prices with the moderating variable dividend policy in banking companies listed on the Indonesian Stock Exchange in 2021-2023. The stock market reflects investors' expectations and perceptions of company performance through share price movements. Method. This research uses a quantitative approach based on positivistic philosophy, which focuses on measuring and testing phenomena empirically. This approach emphasizes that a phenomenon is considered to exist if it can be proven through measurable data. Therefore, the analysis was carried out objectively using quantitative data. This aims to ensure the validity and accuracy of research results. This research uses data from 47 banking companies listed on the Indonesia Stock Exchange. Sample selection was carried out using a purposive sampling method based on certain criteria. As a result, 25 companies were obtained that met the criteria for further analysis. This data is the basis for evaluating the relationship between variables in the study. Results. The results of this research show that: 1) Business Risk has a negative effect on stock prices, 2) Corporate Governance has a negative effect on stock prices, 3) Business Risk has a negative effect on dividend policy, 4) Corporate Governance has a negative effect on dividend policy, 5) Dividend policy weakens the influence of business risk on share prices, and 6) Dividend Policy weakens the influence of Corporate Governance on share prices. Conclusion. Business risk and corporate governance influence stock prices, with dividend policy as a moderating variable. Good corporate governance creates transparency and supports share price stability. A consistent dividend policy provides a positive signal to investors, strengthening the relationship with share prices.